Pengembangan Lembar Kegiatan Peserta Didik (LKPD) Mata Pelajaran Dasar – Dasar Akuntansi dan Keuangan Lembaga pada Sekolah Menengah Kejuruan - Azzahra, Rachmi Yuliani; Ilmi, Yusina Fadla; Mulyati, Budi (FKIP, Universitas Banten Jaya, 2025)
This research was motivated by the lack of learning media in the subject of Basic Accounting and Institutional Finance in the Independent Curriculum. This study aimed to develop a product of Learner Activity Sheets (LKPD) for Basic Accounting and Institutional Finance subjects. This LKPD was prepared using the development research method (Research and Development) using the 4D model. The initial stage of the research was define, this stage is carried out to define the research needs. The design stage was product design. Develop stage, at this stage the initial product was validated by expert validators, material experts and media experts. After being validated and revised, the product was used by students. The last stage was the dessiminate stage, at this stage the product was distributed on a small scale. The data in this study were obtained through expert validation tests and students response questionnaire. Based on the calculation of the material expert validation test, the percentage results showed 83.34% (very feasible), the results of the media expert validation test were 91.67% (very feasible), and the student response was 94.91% (very feasible).